2019
DOI: 10.1002/lary.27912
|View full text |Cite
|
Sign up to set email alerts
|

The association between the Nutrition‐Related index and morbidity following head and neck microsurgery

Abstract: Objectives/Hypothesis Despite consensus that preoperative nutritional assessment is of importance in the head and neck surgical oncology population, it remains unclear how exactly malnutrition is associated with perioperative morbidity especially among those undergoing microvascular surgery. We aimed to study this association to help inform preoperative risk stratification, guide the use of nutritional interventions, and ultimately help prevent malnutrition related morbidity. Study Design Database analysis. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 45 publications
0
31
0
Order By: Relevance
“…17 Analysis with propensity score-matched cohort showed that malnourished group had more frequent pulmonary complications, more frequent blood transfusions, higher rates of venous thromboembolism, and higher 30-day mortality rates. 17 This is in keeping with the findings of our study that suggested that moderate nutritional risk as defined by NRI score less than 97.5 is associated with higher risk for complications. The study provides further evidence for NRI score as a prognostic tool in HNC patients undergoing curative intent treatment.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…17 Analysis with propensity score-matched cohort showed that malnourished group had more frequent pulmonary complications, more frequent blood transfusions, higher rates of venous thromboembolism, and higher 30-day mortality rates. 17 This is in keeping with the findings of our study that suggested that moderate nutritional risk as defined by NRI score less than 97.5 is associated with higher risk for complications. The study provides further evidence for NRI score as a prognostic tool in HNC patients undergoing curative intent treatment.…”
Section: Discussionmentioning
confidence: 97%
“…16 For descriptive statistics, patients were categorized as no malnourishment (>100), mild (97.5-100), moderate (97.5-83.5), and severe (<83.5) risk as per prior studies. 9,11,17 For time-dependent, survival, and treatment complication regression analysis, none and mild risk patients (NRI ≥ 97.5) were combined as a control group to compare with moderate and severe groups (NRI < 97.5) as per the prior studies supporting an NRI cut off value of 97.5, and to account for the small range of NRI scores in the mild risk group (97.5-100). 10,[17][18][19] The primary outcome was the change between the pretreatment NRI score and the posttreatment NRI score.…”
Section: Data Collection and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The ideal body weight (IBW) was calculated for each patient using the Devine formula for men and the Robinson formula for women [11]. The energy demand during the study period was calculated individually for each patient using the ideal weight and the estimate of 30 kcal/kg/day, which was derived from both the ESPEN guidelines for surgical patients and from the national nutritional guidelines of the UK for HNC patients [1,10].…”
Section: Nutrition Deliverymentioning
confidence: 99%
“…Although HNC free flap surgery may have a substantial impact on normal eating, chewing and swallowing, there is a lack of studies contemplating the adequacy of nutrition during the immediate postoperative period. Studies concerning the postoperative nutrition of hospitalized HNC patients have mostly been focusing on the preceding prevalence of malnutrition [11,12] and optimal initiation of oral food intake such as in laryngectomized patients in terms of pharyngocutaneus fistula formation [13][14][15].…”
Section: Introductionmentioning
confidence: 99%